Development of Number Board Media for Early Childhood Pre-Mathematics Introduction - Ulva; Debie Susanti; Irma Yuliantina (UNIB Press, 2025)
Early numeracy skills are essential for supporting cognitive development in early childhood education. Observations at TK Yapis Ash Siddiq in Central Papua indicated that many children aged 5–6 years continued to have difficulty recognising and understanding numbers. Therefore, this study aimed to describe the conditions of numeracy learning among children at TK Yapis Ash Siddiq, develop a number board learning medium suited to early childhood characteristics, assess its feasibility, and test its effectiveness in improving numeracy skills. This research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation. A purposive sampling technique was used to select 12 children aged 5-6 years. A one-group pretest-posttest design was used to measure media effectiveness. Validation results from material and media experts yielded feasibility scores of 90% and 95%, categorised as highly feasible. The average numeracy score increased from 1.6 (on a 4-point scale) to 3.1 (on a 4-point scale), with an N-Gain of 0.64 (medium–high category). Observations also showed that children were highly enthusiastic and actively participated during learning. These results indicate that the number board is both feasible and effective as a learning tool for enhancing early numeracy skills in early childhood education.